STUDI PEMBERDAYAAN WANITA TANI MELALUI USAHA KEBUN KOLEKTIF (Kasus pada Kelompok Swadaya Masyarakat Lestari, Desa Tanjung Seteko, Ogan Ilir) - Sriati, .; KarimYusuf, Abdul; Sucipto, Agus (Indonesian Journal of Socio Economics)
The aim of this research were  to measure the participation level of women farmers at Lestari Society Selfreliance Group and to identify the factors that influence the participation of women  farmers. This research was conducted in the Village of Tanjung Seteko, Sub District of Indralaya, District of Ogan Ilir in May 2005.  The research use case study, where Lestari Society Selfreliance  Group was a case unit.  The sample used census on the whole members of Lestari  Society Selfreliance Group consisted of 17 people.  The data includes primary and secondary data.  The data was tested with score judgment and was analyzed descriptively.  The second objective was explained in a tabulation and description, in terms of exposing the gained results in the form of systematical explanation. The measure results of the participation level of women  farmers on cultivation of collective plantation of hybrid corn showed that 11,76 % on low category, 70,59 % on middle category and 17,65 % on high category.  Thus, the participation level of the women farmers on cultivation of collective plantation of hybrid corn could be categorized on the middle level at average of 2,23 and average score was 13,35.